The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1038/s41598-020-76324-7
|View full text |Cite
|
Sign up to set email alerts
|

Giant refractometric sensitivity by combining extreme optical Vernier effect and modal interference

Abstract: The optical Vernier effect consists of overlapping responses of a sensing and a reference interferometer with slightly shifted interferometric frequencies. The beating modulation thus generated presents high magnified sensitivity and resolution compared to the sensing interferometer, if the two interferometers are slightly out of tune with each other. However, the outcome of such a condition is a large beating modulation, immeasurable by conventional detection systems due to practical limitations of the usable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…An example is the recent work of Gomes et al., where the authors showed that it is possible to combine the optical Vernier effect with mode interference, reaching M ‐factors an order of magnitude higher than what could be reached until now. [ 76 ] Moreover, the method preserves a measurable Vernier envelope, whilst achieving extremely high M ‐factors. The authors reported a record M ‐factor of over 850 and a giant refractive index sensitivity of about 500 000 nm RIU −1 .…”
Section: Final Remarksmentioning
confidence: 99%
“…An example is the recent work of Gomes et al., where the authors showed that it is possible to combine the optical Vernier effect with mode interference, reaching M ‐factors an order of magnitude higher than what could be reached until now. [ 76 ] Moreover, the method preserves a measurable Vernier envelope, whilst achieving extremely high M ‐factors. The authors reported a record M ‐factor of over 850 and a giant refractive index sensitivity of about 500 000 nm RIU −1 .…”
Section: Final Remarksmentioning
confidence: 99%
“…For example, an effective way to improve the detection range of the Vernier effect is to use signal processing technology to expand the envelope periodically [33]. The development of higher sensitivity also can be combined with new modes, such as the use of a low-mode interferometer to modulate the large envelope of the Vernier effect, which allows the excellent wavelength offset performance of the large envelope to be retained [32].…”
Section: Experiments and Discussionmentioning
confidence: 99%
“…In another report by the author, the use of a modal interference combined with extreme optical Vernier effects to produce a measurable envelope while maintaining extremely high magnification is proposed. This method demonstrated the ultra-sensitive fiber refraction with a sensitivity of 500 µm/RIU, and the calculated magnification was higher than 850 times that of normal magnification [32]. Recently, people have also begun to consider signal processing methods to solve the envelope problem.…”
Section: Introductionmentioning
confidence: 99%
“…These sensors are bulky and require a large amount of analyte. Another way to boost S is to utilize the optical Vernier effect in two coupled interferometers. , This method also increases the device footprint as well as the complexity of the sensor design. On the other hand, the FoM is defined as S normalized by the full width at half-maximum (FWHM) of the resonance mode, i.e., FoM = S /fwhm.…”
Section: Introductionmentioning
confidence: 99%